PERITONITIS RESULTING FROM PRIMARY UMBILICAL VEIN CATHETER USE IN NEONATES: A CASE REPORT - Mulandari, Made Melly (E-Jurnal Medika Udayana, 2014)
Primary Peritonitis is an infection of the peritoneal cavity which is common in patients with ascites who are not associated with abdominal disease or retroperitoneal. Cases of primary peritonitis due to umbilical sepsis that occurs from umbilical catheter as many as 8 cases out of 32 cases of newborns who suffered peritonitis. This report discusses the case of primary peritonitis in 22 days neonatal who showed infections which cause used umbilical venous catheter. Imaging finding (BOF) suspected a pneumoperitoneum. Laparotomy surgery on this patient for diagnostic and drainage ascites fluid. Patient  admitted to intensive care (NICU) given fluid therapy, oxygen, and specific antibiotic (Cefoperasone sulbactam + Amikacin for 7 days). After 5 days, the patient’s condition improved, so transferred to the neonatal room.
Keywords: peritonitis, umbilical catheter